Are “10 Grams of Protein” Better than “Ten Grams of Protein”? How Digits versus Number Words Influence Consumer Judgments - Romero, Marisabel; Craig, Adam W; Mormann, Milica; Kumar, Anand (Journal of Consumer Research, 2025)
Abstract Numerical information can be communicated using different number formats, such as digits (“5”) or number words (“five”). For example, a battery product may claim to last for “5 hours” or “five hours.” And while these two formats are used interchangeably in the marketplace, it is not clear how they influence consumer judgments and behavior. Via six experimental studies, two online ad campaigns, and one large secondary dataset analysis, we find that digits, compared to number words, positively affect consumer behavior. We refer to this phenomenon as the number format effect. We further show that the number format effect occurs because consumers feel that digits (vs. number words) are the right way to present numerical information: digits lead to a sense of feeling right that then affects consumer behavior. Finally, we show that the number format effect is amplified when credibility of the source of information is low, and attenuated when source credibility is high. The current research advances knowledge of how numerical information influences consumer judgments and behavior and carries important implications for marketers and policymakers as they communicate numerical information to consumers.